Cybersecurity Concerns & Teleworking in the COVID-19 Era: A Socio-Cybersecurity Analysis of Organizational Behavior (Journal of Advanced Research in Social Sciences, 2020)
This research project examines the relationship between teleworking cybersecurity protocols during the COVID-19 era and employee’s perception of their efficiency and performance predictability.  COVID-19 is the infectious disease caused by the most recently discovered coronavirus and it has been declared a pandemic by the World Health Organization. Since March 2020, many employees in the United States who used operate onsite, have been working from their homes (teleworking) to mitigate the spread of the virus through social distancing. The premise of this research project is that teleworking can transform these employees into unintentional insider threats or UITs. Iinterviews were conducted through video conferencing with nine employees in Virginia, USA to examine the problem. This is an interdisciplinary research project which brings together the disciplines of sociology and computer science. Narrative Analysis was used to unpack the interviews. The major findings from the research efforts demonstrate that employees are trusting of the cybersecurity protocols that their organizations implemented but they also believe they are vulnerable, and that the protocols are not as reliable as in-person working arrangements. While the respondents perceived that the cybersecurity protocols lend to performance predictability, they seem to think it disrupts their efficiency.